Nanotechnology for Sustainable Development 2012
DOI: 10.1007/978-3-319-05041-6_7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of carbon-covered alumina (CCA) supported TiO2 nanocatalysts with enhanced visible light photodegradation of Rhodamine B

Abstract: The anatase phase of titania (TiO 2 ) nanophotocatalysts was prepared using a modified sol gel process and thereafter embedded on carbon-covered alumina supports. The carbon-covered alumina (CCA) supports were prepared via the adsorption of toluene 2,4-diisocyanate (TDI) on the surface of the alumina. TDI was used as the carbon source for the first time for the carbon-covered alumina support system. The adsorption of TDI on alumina is irreversible; hence, the resulting organic moiety can undergo pyrolysis at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Since the flocculation was fast, it was probable that the flocculation occurred mainly through electrostatic interaction (Mahlambi et al 2012). However, the aggregation size induced by the CNF was very small, which was similar to CPAM-L (Fig.…”
Section: +mentioning
confidence: 79%
“…Since the flocculation was fast, it was probable that the flocculation occurred mainly through electrostatic interaction (Mahlambi et al 2012). However, the aggregation size induced by the CNF was very small, which was similar to CPAM-L (Fig.…”
Section: +mentioning
confidence: 79%
“…2b, CS1 holds nanorods structure. It has been reported that 1D-nanostructured semiconductors can be considered as a special paths for efficient transport of electrons and optical excitations [33]. As a result, the photogenerated electron-hole pairs could move effectively to the surface of the photocatalyst to degrade the adsorbed MO molecules, enhancing the photocatalytic efficiency [34].…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%